Neural anti-inflammatory natural product periconianone A: total synthesis and biological evaluation - Kalmode, Hanuman P.; Patil, Suhag S.; Handore, Kishor L.; Athawale, Paresh R.; Dandela, Rambabu; Verma, Abhishek Kumar; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2019)
Total synthesis of periconianone A, an eremophilane-type sesquiterpenoid with impressive neural anti-inflammatory potential, has been accomplished. Diels-Alder/aldol strategy to construct tetrahydro-naphthalene-2,6-dione scaffold, allylic oxidation of dienone using DBU/O-2 and postulated biomimetic aldol reaction to construct 6/6/6 tricyclic system are the highlights of the present synthesis. Furthermore, the synthesized (+/-)-periconianone A and two close analogs were tested for their neural anti-inflammatory activity using various assays. In the course of our study we found a structurally simplified analog is superior to (+/-)-periconianone A.
Keywords: Aldol; Allylic oxidation; Biological evaluation; Cytotoxicity; Diels-Alder; Periconianone A

Copper-mediated [3+2] oxidative cyclization of oxime acetate and its utility in the formal synthesis of fentiazac - Jadhao, Nitin L.; Musale, Harish B.; Gajbhiye, Jayant M.; Humne, Vivek T. (Organic and biomolecular chemistry, 2024)
A new protocol for the direct synthesis of 2-aminothiazole has been developed from oxime acetate and readily available sodium thiocyanate using a copper catalyst. The present transformation has good functional group tolerance. Various thiazoles were smoothly synthesized in good to excellent yields. The applicability of the present method has been extended to the formal synthesis of the non-steroidal and anti-inflammatory drug, fentiazac via the Sandmeyer reaction and Suzuki coupling. The direct synthesis of 2-aminothiazole has been developed from oxime acetate using a copper catalyst. The applicability of the present method is used in the formal synthesis of fentiazac.
Keywords: Biological evaluation; C-H functionalization; Vinylazides

Regio selective synthesis of pyrazole derivatives of 5-chloro-2-methoxy phenyl hydrazide and their biological evaluation - Bavishi, Abhay; Vala, Hardev; Swami, Sagar; Thakrar, Shailesh; Shah, Anamik; Sarkar, Dhiman (Journal of Heterocyclic Chemistry, 2025)
Present study involves synthesis of derivatives of (5-chloro-2-methoxyphenyl) (5-alkyl-3-(substituted) (phenyl/alkyl)-1H-pyrazol-1-yl) methanones. Structural elucidation of the synthesized compounds was depicted by the data of 1H and 13C NMR, IR, and Mass spectral analysis. The newly synthesized compounds 1a-1d and 2a-2i were screened in vitro against Mycobacterium tuberculosis H37Ra using an established XRMA protocol. Among the screened compounds, 2d, 2f, and 2h showed good percent inhibition against the active stage of M. tuberculosis H37Ra 80.77, 55.70, and 79.54, respectively, at 30 mu g/mL of inhibitor concentration. Further in secondary screening, compound 2d exhibited significant antitubercular activity on the active stage of M. tuberculosis H37Ra with IC50 of 0.208 mu g/mL. The synthesized compounds were also screened for antibacterial activity and found no significant activity against Gram-positive Bacteria Bacillus subtitles and Staphylococcus aureus and Gram negative bacteria Pseudomonas aeruginosa and Escherichia coli at 30 mu g/mL, which confirms the specificity of inhibitory activity against M. tuberculosis and more selectively against the active stage. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.
Keywords: 5-chloro-2-methoxy phenyl hydrazide; antibacterial activity; Antitubercular activity; Biological evaluation; H37Ra; hydrazide; Pyrazole